2015
DOI: 10.1111/1742-6723.12516
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of hospital‐wide reform at improving access and flow: Impact on time to antibiotics in the emergency department

Abstract: Following implementation of hospital-wide reform directed at mitigating ED overcrowding through improved access and flow, times to administration of antibiotics were significantly reduced. These findings suggest that improved quality of care in this area may be achieved with processes aimed at improved hospital access and flow. Ongoing evaluation and vigilance is necessary to ensure sustainability and drive further improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
1
12
0
Order By: Relevance
“…Operational level strategies and tactics• Developing evidence-based admission criteria [21]• Implementing Electronic Blockage System (EBS) [99]• Implementing smoothing strategy [100]• Using capacity alert escalation calls [20]• Applying Discrete Event Simulation (DES) model [22]• Improving leadership of ED [101]• Implementing contingency strategy [102]• Using management-support multimodal hospital-wide interventions [103]• Implementing four-hour-rule for emergency care [104]• Introducing of Stat Lab [105]• Implementing Code Help Regulation [106]• Using a dashboard to provide real-time information about crowding [107]c. Service delivery process• Acute care emergency surgery service provision [108]• Whole week emergency service delivery [109]• Implementing triage by physicians [110]• Introducing efficient patient discharging process [111]• High-turnover utility bed management [112]• Implementing Timely Quality Care [113]• Implementing an improved ED patient flow [114]d. Other services• Enhanced primary care [21, 115]• Optimizing translation services [21]e.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Operational level strategies and tactics• Developing evidence-based admission criteria [21]• Implementing Electronic Blockage System (EBS) [99]• Implementing smoothing strategy [100]• Using capacity alert escalation calls [20]• Applying Discrete Event Simulation (DES) model [22]• Improving leadership of ED [101]• Implementing contingency strategy [102]• Using management-support multimodal hospital-wide interventions [103]• Implementing four-hour-rule for emergency care [104]• Introducing of Stat Lab [105]• Implementing Code Help Regulation [106]• Using a dashboard to provide real-time information about crowding [107]c. Service delivery process• Acute care emergency surgery service provision [108]• Whole week emergency service delivery [109]• Implementing triage by physicians [110]• Introducing efficient patient discharging process [111]• High-turnover utility bed management [112]• Implementing Timely Quality Care [113]• Implementing an improved ED patient flow [114]d. Other services• Enhanced primary care [21, 115]• Optimizing translation services [21]e.…”
Section: Resultsmentioning
confidence: 99%
“…The practice of triage by physicians reduce the patients LWBS in the EDs [110]. Other interventions which contribute to the reduction of crowding included whole week emergency service delivery [109] and implementing Timely Quality Care [113]. Other services: Improving other services such as enhancing primary care [21, 115], optimizing translation services concerning patients’ issues [21] and an engagement on specialists in the outpatient environment [116, 117] contribute to the reduction of ED LOS and crowding. Premises: The high emergency patient flow forced the healthcare delivery system to address related issues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…15 In the currently published research literature, only 2 observational studies have reported prospective time-to-treatment measurement. 23,24 However, both studies did not actually compare medication documentation time with medication administration time. Roman et al 23 described the effects of a hospital-wide reform to improve timely delivery of antibiotics, while Miner et al 24 only investigated the effects of oral vs intravenous opioids on medication times.…”
Section: Introductionmentioning
confidence: 99%